Etika Profesi Penerbangan Berbasis Virtue Ethics di Indonesia - Dinar Dewi Kania; Dian Artanti Arubusman; Mustika Sari (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The purpose of the study is to analyze factors to prioritize the development of aviation professional ethics based on virtue ethics in Indonesia and to decide which best suitable strategy to accomplish the purpose. The data was taken from 8 (eight) aviation and ethics expertise and practitioners. The method of data analysis used Analytic Network Process (ANP) and Super Decisions software was employed to process the data.The result shows that the best and most effective strategy in developing aviation professional ethics based on virtue ethics in Indonesia is by applying the Virtous Leadership. The Virtue Ethics Approach is bound much with moral examples. It means, to ensure the professional and ethical employees in an organization, first thing to do is to assure that the leaders and managers of the organization can give examples and do the obligation with high commitment based on virtues values such as courageous character, honesty, and other cardinal virtues.